Covid-19 Vaccine Hesitancy: Frequency and causes among Population of Lahore - Najma Shoaib, Muhammad Atif Qureshi, Muhammad Zahid Latif (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Covid-19 vaccine hesitancy is prime hurdle in control and eradication of Covid-19 pandemic. The rapid Procedure of development of new vaccines resulted in a lot of false information and rumors leading to decrease trust of the public in the safetyand effectiveness of the vaccine. Aim: To study the frequency and causes of Covid-19 vaccine hesitancy amid population of Lahore. Methods: This cross sectional study design was done on a sample of 385 participants from lahore were included in the study. Frequency and causes were recorded on the prescribed questionnaire. Results: Frequency of hesitancy was found to be 41.7%. 12.8% had doubts related to efficacy and safety of the vaccine. 9.9% were of the view that the risks of the vaccine are greater than its benefits. 5.7% assumed that vaccines were promoted for gains of pharmaceutical companies. 4.4% were concerned about the immediate side effects of the vaccine. 2.6% responded by saying that vaccine was not recommended by health professionals. 2.3% had myths related to vaccine. And lastly, 1.63% said vaccine was not available free of cost. Conclusion: Hesitancy of covid-19 vaccine is seen more in illiterate people and the main cause of hesitancy is uncertainty related to protection and efficacy of covid-19 vaccine. Keywords: Covid-19 vaccine, hesitancy, myths, safety and efficacy, uncertainty, doubt, well being ,protection